Taxonomic assessment of the shrimp Macrobrachium denticulatum Ostrovski, da Fonseca & da Silva-Ferreira, 1996 (Decapoda: Palaemonidae) using molecular and morphological data: a comparison with M. olfersii (Wiegmann, 1836) - Cardim, Robert Wagner Dos Santos; Mota, Thaís Arrais; Carvalho, Fabrício Lopes (Zootaxa, 2025)
The freshwater shrimp Macrobrachium denticulatum Ostrovski, da Fonseca & da Silva-Ferreira, 1996 is endemic to São Francisco River, Northeastern Brazil, and exhibits high morphological similarity to the widespread Macrobrachium olfersii (Wiegmann, 1836). The morphological differences observed between these species consist of variations in the second pair of pereiopods, which have been regarded as intraspecific variation in M. olfersii. Therefore, this study aimed to analyze the variability and validity of the diagnostic morphological characteristics of M. denticulatum in conjunction with molecular data obtained from the mitochondrial 16S rRNA gene. In total, 144 individuals were examined, of which 21 were identified as M. denticulatum (all of them from São Francisco Basin) and 123 as M. olfersii. The number of teeth on the cutting edge of the fixed finger ranged from two to five small teeth followed by a larger distal tooth in both species, indicating an overlap in the primary diagnostic characteristics used to differentiate these species. None of the diagnostic characters described to date for differentiating these two species are consistent. A total of 43 sequences were analyzed, including five new sequences, among them a paratype of M. denticulatum. The phylogenetic tree generated by maximum likelihood and Bayesian analyses demonstrated clear genetic differentiation between the two species, validating M. denticulatum from a molecular standpoint. As none of the diagnostic morphological characters proposed in the literature or analyzed in this study were found to be effective for the morphological differentiation of these species, M. denticulatum is herein considered to be a cryptic species.